Answer:
Step-by-step explanation:
4 (x + 3) = 2x + 8 <----"four times the sum of a number and three is equal to eight more than twice the number."
Second, we want to solve the equation:
4 (x + 3) = 2x + 8
4x + 12 = 2x + 8
2x + 12 = 8 <-------subtract 2x from both sides of the equation.
2x = -4 <-------subtract -12 from both sides
x = -2 <-------divide both sides by 2 which leaves a negative answer
Third, we want to check the answer by substituting the value of -2 for x in the original equation.
4 (x + 3) = 2x + 8
4 (-2 +3) = 2(-2) + 8
-8 + 12 = -4 + 8
4 = 4
4 (x + 3) = 2x + 8 <----"four times the sum of a number and three is equal to eight more than twice the number."
Second, we want to solve the equation:
4 (x + 3) = 2x + 8
4x + 12 = 2x + 8
2x + 12 = 8 <-------subtract 2x from both sides of the equation.
2x = -4 <-------subtract -12 from both sides
x = -2 <-------divide both sides by 2 which leaves a negative answer
Third, we want to check the answer by substituting the value of -2 for x in the original equation.
4 (x + 3) = 2x + 8
4 (-2 +3) = 2(-2) + 8
-8 + 12 = -4 + 8
4 = 4